Survival following salvage therapy for primary refractory peripheral T‐cell lymphomas (PTCL). Issue 3 (18th December 2017) - Zhang, Janie Y.; Briski, Robert; Devata, Sumana; Kaminski, Mark S.; Phillips, Tycel J.; Mayer, Tera L.; Bailey, Nathanael G.; Wilcox, Ryan A.
Abstract: Optimal salvage therapy for primary refractory peripheral T‐cell lymphomas (PTCL) and the role of hematopoietic stem cell transplant (SCT) remain poorly defined. We conducted a retrospective review of clinical outcomes and prognostic factors in a single‐center cohort of 93 patients with primary refractory PTCL, defined as progression during first‐line therapy or relapse within 6 months of its completion. Clinical outcomes were poor in this population, with median event‐free survival (EFS) of 3.5 months, median overall survival (OS) of 9.1 months, and 34% 3‐year survival. Outcomes were comparable in patients who progressed through first‐line therapy and patients who achieved CR/PR and subsequently relapsed within 6 months. A majority exhibited high‐risk features and had intermediate to high risk IPI, which correlated with inferior outcomes. There was no difference in outcomes between patients who received single‐agent salvage regimens and patients who underwent traditional, multi‐agent salvage regimens. Thus, participation in well‐designed clinical trials should be encouraged in this population. Additionally, there may be a trend toward improved EFS and OS in patients who underwent autologous or allogeneic SCT compared to patients who achieved CR or PR but were not transplanted.